EFEKTIVITAS PENERAPAN MODEL PEMBELAJARAN EVERYONE IS A TEACHER HERE TERHADAP KEMAMPUAN BERFIKIR KRITIS SISWA - Dewi, Chika Septilia; Aminuyati, Aminuyati; Rosyid, Rum (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractThe purpose of this research is to know the critical thinking ability of students in IPS grade VIII SMPN 2 Simpang Hilir Regency of North Kayong. By applying the Everyone Is A Teacher Here learning model with students studying the Conventional model. problem formulation in this research How Effectiveness of Learning Model Applying Everyone is a Teacher Here Against the ability to Think Critical Students In Class IPS Class VIII SMPN 2 Simpang Hilir Kabupaten Kayong Utara. The research method used is Quasi Experiment and NonEquivalent Control Group Design research design. Data collection techniques use observation, interviews, and tests. Data collection tools, in the form of observation sheets, interview guides and tests. Based on the analysis in obtaining the data in the form of posttest result of the students of the experimental class of 73.51 and the posttest control class value of 65.94. From the data it can be seen that the students' critical thinking ability in the experimental class is higher than the control class. This shows that Every Is A Teacher Here learning model is effective in IPS learning activities. The aim was proved in the t test, that there was a difference in critical thinking ability of students with the tcount value> ttable (4,702> 1,785) was determined that Ha was accepted and H0 was rejected.Â Keywords: Critical Thinking Capability, Everyone Is A Teacher Here